CRISPR-Cpf1 mediates efficient homology-directed repair and temperature-controlled genome editing. Issue 1 (December 2017) - Moreno-Mateos, Miguel; Fernandez, Juan; Rouet, Romain; Vejnar, Charles; Lane, Maura; Mis, Emily; Khokha, Mustafa; Doudna, Jennifer; Giraldez, Antonio
Abstract Cpf1 is a novel class of CRISPR-Cas DNA endonucleases, with a wide range of activity across different eukaryotic systems. Yet, the underlying determinants of this variability are poorly understood. Here, we demonstrate that LbCpf1, but not AsCpf1, ribonucleoprotein complexes allow efficient mutagenesis in zebrafish andXenopus . We show that temperature modulates Cpf1 activity by controlling its ability to access genomic DNA. This effect is stronger on AsCpf1, explaining its lower efficiency in ectothermic organisms. We capitalize on this property to show that temporal control of the temperature allows post-translational modulation of Cpf1-mediated genome editing. Finally, we determine that LbCpf1 significantly increases homology-directed repair in zebrafish, improving current approaches for targeted DNA integration in the genome. Together, we provide a molecular understanding of Cpf1 activity in vivo and establish Cpf1 as an efficient and inducible genome engineering tool across ectothermic species. Cpf1 is a promising addition to the CRISPR toolkit but displays wide variability of activity in different eurkaryotes. Here the authors identify temperature as a modulator of activity and use this to efficiently edit ectothermic vertebrate species.